Grass abundance maintains positive plant–arthropod diversity relationships in maize fields and margins in South Africa. (19th October 2016) - Botha, Monique; Siebert, Stefan J.; van den Berg, Johnnie
Abstract: The large‐scale cultivation of crops may lead to biodiversity decreases as a result of habitat loss and degradation of natural habitats. A popular strategy for enhancing insect diversity in intensively cultivated habitats involves maintaining plant diversity in field margins by means of sown grass and wildflower strips. Despite extensive cultivation of maize/corn (approximately 3.1 million ha) in the grassy biomes of South Africa, little effort has been made to understand whether plant groups maintain insect biodiversity within these agro‐ecosystems. The diversity relationships between three prominent guilds of arthropods (herbivores, parasitoids and predators) and three large plant families (Asteraceae, Fabaceae and Poaceae) are described at regional scale across the Grassland and Savanna Biomes of South Africa. The results obtained indicate general positive relationships between plant and arthropod diversity of the lower vegetation layers (≤2 m). An increased abundance of members of the grass family (Poaceae) led to significantly higher invertebrate numbers in maize fields and adjacent vegetation. This suggests that grasses play a significant role in supporting arthropod diversity within these agro‐ecosystems. When considering farm design in maize‐agro‐ecosystems, our results indicate that maintaining grassy natural vegetation patches adjacent to actively cultivated maize fields may be sufficient to maintain and conserve arthropod diversity within agricultural landscapes.